Development and Validation of an LC-MS/MS Method for the Simultaneous Quantification of Abiraterone, Enzalutamide, and Their Major Metabolites in Human Plasma. Issue 3 (June 2017) - van Nuland, Merel; Hillebrand, M. J. X.; Rosing, H.; Schellens, J. H. M.; Beijnen, J. H.
Abstract : Background: Abiraterone acetate and enzalutamide are 2 novel drugs for the treatment of metastatic castration-resistant prostate cancer. The metabolism of these drugs is extensive. Major metabolites are N- desmethyl enzalutamide, enzalutamide carboxylic acid, abiraterone N-oxide sulfate, and abiraterone sulfate; of which N - desmethyl enzalutamide is reported to possess antiandrogen capacities. A liquid chromatography-tandem mass spectrometry method for simultaneous quantification of abiraterone, enzalutamide, and the main metabolites has been developed and validated to support therapeutic drug monitoring. Methods: Human plasma samples of patients treated with abiraterone or enzalutamide were harvested at the clinic and stored at −20°C. Proteins were precipitated by acetonitrile, and the final extract was injected on a Kinetex C18 column and separated with gradient elution. Analytes were detected by liquid chromatography-mass spectrometry (Triple Quad 6500). Results: The method was validated over various linear ranges: 1–100 ng/mL for abiraterone, 5–500 ng/mL for enzalutamide and enzalutamide carboxylic acid, 10–1000 ng/mL for N- desmethyl enzalutamide, 30–3000 ng/mL for abiraterone N-oxide sulfate, and 100–10, 000 ng/mL for abiraterone sulfate. Intra-assay and interassay variabilities were within ±15% of the nominal concentrations for quality control samples at medium and high concentrations and within ±20% at the lower limit of quantification, respectively. Conclusions: The described method for simultaneous determination of abiraterone and enzalutamide was validated successfully and provides a useful tool for therapeutic drug monitoring in patients treated with these agents.